Comparison of Conservatism in Islamic And Conventional Banks in Indonesia And Malaysia - Nanda Putri Ghassani Fildzah, Dini Rosdini, (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
Malaysia and Indonesia are two of the ten countries with the largest total assets of Islamic financial markets in the world. The religiosity of a company can influences one of the qualities of accounting. The accounting quality of a company can be measured from accounting conservatism. This study aims to determine the comparison of conservatism between Islamic banks and conventional banks. The samples are Islamic banks and conventional banks in Indonesia and Malaysia from 2013 to 2017. The samples are 13 Islamic banks and 45 conventional banks so that the total sample is 290 observations. Data analysis using pooled least square regression. The result showed that conventional banks in Indonesia tend to be more conservative compared to sharia banks and sharia banks in Malaysia tend to be more conservative compared to conventional banks. Furthermore, changes in non-performing loans and changes in loan charge-offs have positive effect on conservatism.